Circular cavity with an arbitrary varying dielectric constant - Сахненко, Н.К. (Radiotekhnika, 2012)
The problem of the whispering gallery mode transformation in a thin disk cavity due to the change in the time of the material dielectric constant is theoretically investigated. Under jump changes in refractive index, the running wave of the whispering gallery transforms into the superposition of the transmitted and reflected  resonator modes but their amplitudes are negligibly small in comparison with the amplitude of the wave the whispering gallery transmitted in time. In this case its frequency and amplitude changes. In the step-periodic time-varying medium it is possible to control the amplitude of the whispering gallery mode that, depending on the values of the parameters, speeds up or slows down the process of the radiation of modes. This effect increases with the increase in the modulation depth.